1992
DOI: 10.2307/2329101
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy and Insider Trading: Differences Between Exchange-Listed and OTC Firms

Abstract: Over the two-year period prior to the bankruptcy announcement, insider trading is significantly greater for OTC bankrupt firms, but not for exchange-listed firms, than for an industry-size matched sample of nonbankrupt firms. In addition, the level of insider selling increases over the final five months leading to the first public announcement of OTC firms. Finally, firms displaying the most negative price reaction over the announcement period are found to have a significantly larger proportion of insider sell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 2 publications
0
13
1
Order By: Relevance
“…In Table VI, we test the sensitivity of the results in Tables IV and V using two measures of abnormal inside trading similar to those used in Seyhun (1990), Karpoff and Lee (1991), Gosnell, Keown, and Pinkerton (1992), Lee et al (1992), Gombola, Lee, and Liu (1997), and Seyhun and Bradley (1997). Abnormal insider trading is measured by an IPO firm's insider net sales minus its size and book‐to‐market matched firm's insider net sales, where insider net sales are defined as insider sales minus insider purchases.…”
Section: Measures Of Abnormal Insider Tradingmentioning
confidence: 99%
“…In Table VI, we test the sensitivity of the results in Tables IV and V using two measures of abnormal inside trading similar to those used in Seyhun (1990), Karpoff and Lee (1991), Gosnell, Keown, and Pinkerton (1992), Lee et al (1992), Gombola, Lee, and Liu (1997), and Seyhun and Bradley (1997). Abnormal insider trading is measured by an IPO firm's insider net sales minus its size and book‐to‐market matched firm's insider net sales, where insider net sales are defined as insider sales minus insider purchases.…”
Section: Measures Of Abnormal Insider Tradingmentioning
confidence: 99%
“…Although regulatory deterrents to illegal insider trading exist, several studies suggest that corporate insiders do earn positive abnormal returns on their trades, including those trades surrounding important firm-specific events. For example, Seyhun and Bradley (1997) and Gosnell, Keown, and Pinkerton (1992) found that insiders exhibit abnormal selling behavior prior to bankruptcy. Park, Jang, and Loeb (1995) found that insiders trade profitably around earnings announcements.…”
Section: Prior Literature and Regulatory Backgroundmentioning
confidence: 99%
“…Loderer and Sheehan (1989) observe no significant decline in insiders' percentage stock ownership prior to bankruptcy for a sample of firms that filed for Chapter 11 during 1971 to 1985, whereas Gosnell, Keown, and Pinkerton (1992) report significantly greater insider selling activity for OTC bankrupt firms over the period 1985 to 1987.…”
mentioning
confidence: 91%